2015
DOI: 10.1016/j.egypro.2015.07.504
|View full text |Cite
|
Sign up to set email alerts
|

Examining a Pretty Simple and Low Cost Method for Modeling of Biogas Production from Biodegradable Solids

Abstract: This paper evaluates the application of consecutive multistage first order kinetics for mathematical modeling of biogas generation trend during anaerobic digestion (AD) of typical farm-based biodegradable solids within batch reactors. The input parameters of the model are mass of biodegradables (as VM), initial content of total volatile fatty acids (TVFA) and recorded values of biogas or methane production. Multistage consecutive equations of first order reaction in combination with numerical solution procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The applicability of a first-order model depends to a large extent on the characteristics and quality of inoculums and that some of the variability in the kinetic constants in models is dictated by the inoculum (Neves et al 2008). The kinetic of CH 4 production from fiber digestion has previously been modeled as a first-order reaction (Kang et al 2014;Adl et al 2015;Castano 2012). However, the comparison of the results from this study with values of the reaction rate constant reported in literature should be conducted cautiously because some studies report the first-order kinetic of the hydrolysis step rather than the entire methane production process.…”
Section: Modeling Kinetics Of Methane Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of a first-order model depends to a large extent on the characteristics and quality of inoculums and that some of the variability in the kinetic constants in models is dictated by the inoculum (Neves et al 2008). The kinetic of CH 4 production from fiber digestion has previously been modeled as a first-order reaction (Kang et al 2014;Adl et al 2015;Castano 2012). However, the comparison of the results from this study with values of the reaction rate constant reported in literature should be conducted cautiously because some studies report the first-order kinetic of the hydrolysis step rather than the entire methane production process.…”
Section: Modeling Kinetics Of Methane Productionmentioning
confidence: 99%
“…Analogously, adaptation and enrichment of mixed anaerobic culture could be used to develop and intensify the lignocellulose (cellulose and hemicellulose) degrading activity in the culture. Although some studies reported biomethane production from lignocellulosic substrates at mesophilic and thermophilic conditions (Adl et al 2015;Janke et al 2015;Kang et al 2014), very few studies (Saady and Massé 2013) have been published on psychrophilic anaerobic digestion of cellulose and hemicellulose. Little is known about the culture kinetics when integrating low temperature with feeding lignocellulose substrate.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the substrate composition, amount of substrate to be treated, and process economy, a plug flow reactor was used because it is known for its lower cost, more stable performance, and ability to withstand environmental stress [23]. Moreover, researchers have also investigated the effectiveness of plug flow reactors on organic substrates with solid content in the range of 11-14% total solids (TS) [24,25]. Biogas production in a plug-flow reactor may be more favorable than in a typical reactor [26], and the role of trace elements in a plug-flow reactor may be different, but this is unknown at this time.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing interest and investment in the biogas production industry, modelling is paramount for a better understanding of the anaerobic digestion process ( Gerber and Span, 2008 ; Gustafsson et al, 2020 ). The determination of the degradation kinetics and the maximum volume of biogas that can be extracted from a given substrate is essential in reactor design and performance control ( Adl et al, 2015 ). These parameters are obtained from anaerobic digestion batch assays, which can be quite time-consuming due to long retention times.…”
Section: Introductionmentioning
confidence: 99%